2009
DOI: 10.1021/np900027m
|View full text |Cite
|
Sign up to set email alerts
|

Lactones from Angiopteris caudatiformis

Abstract: Angiopterlactones A (1) and B (2), two unique lactones, and three known lactones, osmundalactone (3), osmundalin (4), and 3,5-dihydroxy-gamma-caprolactone (5), have been isolated from the rhizome of Angiopteris caudatiformis. The structures of 1 and 2 were determined by NMR and MS methods, and the structure of 2 was confirmed by X-ray crystallography. The absolute configurations of 1 and 2 were assigned by application of the CD excitation chirality method and the modified Mosher's method. Compound 1 was slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
1
42
0
1
Order By: Relevance
“…The zebrafish embryo teratogenicity assays were evaluated according to the described methods [4,5]. The agrochemical assays were evaluated by the methods described previously [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The zebrafish embryo teratogenicity assays were evaluated according to the described methods [4,5]. The agrochemical assays were evaluated by the methods described previously [15]. …”
Section: Methodsmentioning
confidence: 99%
“…reported that the most abundant compounds in the LPH volatile oil were 1,8‐cineole, carvone and limonene. Yu et al . also found that, the ACH volatile oil was characterized by the dominant presence of isocaryophyllene and germacrene B.…”
Section: Resultsmentioning
confidence: 92%
“…Angiopterlactones are diverse class of lactones integrated with ether linkage, which was isolated as metabolites from the plant Angiopteris caudatiformis by Zou and co‐workers in 2009 and projected structures of angiopterlactone A 1 , angiopterlactone B 2 , along with osmundalctone 4, osmundalin 3 and 3–5 dihydroxy γ‐caprolactone 5 . Authors did not demonstrated stereochemistry of lactone 3 , 4 and 5 in isolation paper . Among all these compounds only angiopterlactone A exhibits cytotoxic activity against HeLa cells, while osmundalactone and osmundalin shows insecticidal activity .…”
Section: Introductionmentioning
confidence: 99%
“…Authors did not demonstrated stereochemistry of lactone 3 , 4 and 5 in isolation paper . Among all these compounds only angiopterlactone A exhibits cytotoxic activity against HeLa cells, while osmundalactone and osmundalin shows insecticidal activity . Indistinguishable lactone 1‐(5‐oxotetrahydrofuran‐2yl) ethyl 2‐phenyl acetate 6 was isolated from fungus Nigrospora sphaerica in 2009 by Pei and et al .…”
Section: Introductionmentioning
confidence: 99%